Small Atom Doping: A Synergistic Strategy to Reduce SnZn Recombination Center Concentration in Cu2ZnSnSe4. Issue 11 (9th September 2022) - Jimenez-Arguijo, Alex; Navarro Güell, Alejandro; Sanchez, Yudania; Malerba, Claudia; Valentini, Matteo; Becker, Pascal; Choubrac, Leo; Unold, Thomas; Jehl Li-Kao, Zacharie; Giraldo, Sergio; Saucedo, Edgardo
Abstract : Kesterite Cu2 ZnSnS x Se4− x (CZTSSe) is among the most promising inorganic Earth‐abundant thin‐film photovoltaic technologies, although currently, the larger voltage deficit compared with more mature chalcogenide technologies is hampering solar‐to‐electricity conversion efficiency progress in these materials. Most of the latest reports agree on the CZTSSe defect structure as the main limitation for the open‐circuit voltage. Small atom doping is suggested as an interesting strategy to reduce the concentration of defects without affecting secondary phase formation. Herein, an innovative approach based on the introduction of LiAlH4 and its further decomposition during the selenization process of CZTSe precursors, as a pathway for hydrogen and lithium/alkali transient doping, is explored. This process shows a strong beneficial influence on the crystal growth and solar cell device performance, especially with a significant improvement in V oc and fill factor. A reduction of nonradiative recombination and a remarkable fourfold increase in the carrier lifetime correlating with the reduction of the open‐circuit voltage ( V oc ) deficit below 330 mV is demonstrated. A mechanism on how small atoms (Li and H) interact to reduce the concentration of SnZn recombination centers while keeping doping relatively unchanged is proposed, opening fundamental perspectives for the simple and universal transient doping of thin‐film chalcogenide compounds. Abstract : Due to the strong detrimental effects and the complexity of secondary phases in Cu–Zn–Sn–Se systems, changes on the defect structure of kesterite absorbers with different treatments have been disregarded. Herein, small atom doping is explored as a pathway to engineer the defect structure of kesterite materials, leading to significant efficiency improvements without modifying the secondary phase formation.